"Selling Poverty" on Kuaishou: How entrepreneurialism disciplines Chinese underclass online participation. Issue 3 (September 2022) - Hou, Jiaxi; Zhang, Yanhui
The meanings of being "underclass" in China are increasingly ambivalent when various disadvantaged social groups also get access to digital platforms which become more and more influential in not just facilitating people's economic and cultural practices online but also mediating, distorting, and reshaping these processes. Using critical techno-cultural discourse analysis about how the underclass represent poverty and themselves by creating short videos and performing live-commerce on Kuaishou, this study finds that digital entrepreneurialism becomes an interlocking governmentality to discipline the underclass' online participation. Afforded by the platform and operationalized by multiple networked actors, entrepreneurialism incorporates the underclass in the digitally mediated productive relationship and at the same time disciplines their online representation and exploits the involved entities through both platform labor and monetary investments to cultivate an underclass entrepreneurial subject. Although claiming to include and empower the diversified Chinese underclass, digital platforms actually reproduce the underclassness by mobilizing the calculated conformity among the underclass to experience the intertwining online and offline inequalities through digital entrepreneurship. Nonetheless, nuances of minor narratives still exist in the digitally mediated self-representation.